Mononuclear cell collection for extracorporeal photochemotherapy: a study comparing an automatic and a semiautomatic apheresis device. Issue 9 (10th January 2013) - Del Fante, Claudia; Scudeller, Luigia; Viarengo, Gianluca; Cervio, Marila; Perotti, Cesare
<x xml:space="preserve">Abstract</x> Background Extracorporeal photochemotherapy (ECP) is an effective cell therapy employed in several diseases, including graft‐versus‐host disease (GVHD) and organ rejection after transplantation. When ECP is performed using the off‐line technique, mononuclear cell (MNC) collection by leukapheresis is necessary for further manipulation. Semiautomated apheresis systems require experienced personnel to obtain a good MNC collection; an automated device, able to efficiently collect MNCs with high purity, is desirable. We compared the semiautomated COBE Spectra MNC and the new automated Spectra Optia v.5.0 MNC (Terumo BCT) devices in terms of efficacy and safety. Study Design and Methods Adult patients with GVHD or bronchiolitis obliterans syndrome (BOS) after lung transplant undergoing ECP at our center were alternatively assigned, within the same ECP cycle (composed by two procedures each), to MNC collection with either device. Patients' characteristics, procedure, and product‐related variables were compared. Results Thirty‐nine patients (24 with GVHD and 15 with BOS) underwent a total of 126 ECP procedures, with good compliance to both devices. Product volume and platelet (PLT) and red blood cell contamination were significantly lower with the Spectra Optia. MNC collection efficiency (CE), purity, and PLT loss were similar between the two devices, while white blood cells CE was in favor of the COBE Spectra. Conclusion The Spectra Optia device proved to be a good option for MNC collection in the difficult ECP setting, since it ensures high‐quality MNC collection, while at the same time saving personnel's time, guaranteeing optimal monitoring and care to this frail patient population.